Hubungan Antara Kepercayaan Diri dan Kemampuan Komunikasi Interpersonal pada Siswa Korban Bullying - Meilia; Siti Fitriana; Vesti Fresdiyati (Universitas Muhammadiyah Metro, 2024)
The purpose of this study was to determine the relationship between self-confidence and interpersonal communication skills among students who were victims of bullying at junior high schools in the SMK Yayasan Pharmasi semarang. The type of research used is quantitative research with an ex post facto research design. The data collection tool used is the self-confidence scale and interpersonal communication scale. The sample technique uses a proportional stratified random sampling technique. Then testing the hypothesis that is using Spearman rank correlation analysis. Confidence scale totaling 45 items has a reliability value of 0.946. Furthermore, the confidence scale consists of 47 items having a reliability value of 0.951. The self-confidence of students who were victims of bullying in junior high schools in the SMK Yayasan Pharmasi semarang region was in the moderate category (M = 129.2; SD = 40.4) and interpersonal communication among students who were victims of bullying in Middle School in the SMK Yayasan Pharmasi semarang region was in the medium category (M = 133.6 ; SD = 40.3). On the results of the Spearman rank correlation test, the result is R = 0.844 which shows that self-confidence has a relationship with interpersonal communication in students who are victims of bullying in junior high schools in the SMK Yayasan Pharmasi semarang region.